Nazist och autist - men ingen terrorist? En fallstudie med TRAP-18 - Bech-Jansen,Harald; Gidlund,Åsa (2023)
This study investigates how the TRAP-18 instrument can be used to identify and prioritize threats from lone actor terrorists by applying the framework on a case of a Swedish man convicted of weapons offenses and crimes against the law on flammable and explosive substances. This case is a contribution to the increasing number of studies using TRAP-18, due to the fact that the individual studied is not convicted of, or has committed, any act of terrorism. The study finds that the perpetrator fulfils a majority of the indicators of TRAP-18, and that TRAP-18 could be a useful tool for authorities to prioritize threats from lone actors. However, the authors of this study question the tool’s usefulness in identifying potential lone actor terrorists.
Keywords: TRAP-18; Terrorism; Sweden; Warning; Threats; Warning behaviour; Characteristics; Swedish Security Service; Lone-actor; National security